Transglutaminase-catalyzed incorporation of [2, 5-3H]histamine into a Mr 84000 particulate protein in pancreatic islets. Issue 1 (February 1989) - Gomis, Ramon; Casanovas, Angeles; Malaisse, Willy J.
Abstract : Rat pancreatic islet homogenates catalyze the incorporation of [2, 5 −3 -H]histamine into endogenous proteins recovered in both the stacking gel and a Mr 84000 protein separated by polyacrylamide electrophoresis. The labelling of these proteins represents a Ca 2+ -dependent process inhibited by glycine methylester, but not sarcosine methylester, and enhanced after preincubation of the islets at a high concentration of D-glucose. Although transglutaminase activity is found in both soluble and particlate subcelluler fractions, the endogenous transglutaminase substrates were located mainly in paarticulate, possibly membrane-associated, material.